2015
DOI: 10.1111/vde.12198
|View full text |Cite
|
Sign up to set email alerts
|

Review: Role of genetics and the environment in the pathogenesis of canine atopic dermatitis

Abstract: It is becoming clear that canine AD is genotypically complex and influenced by a variety of environmental factors. Well-designed studies with sufficient statistical power will be critical to identify the complex genetic and environmental factors involved in disease development and progression. Recognition of such factors may help to identify new targets for therapy and enable better disease prevention and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 88 publications
1
53
1
4
Order By: Relevance
“…The reason for this is unclear. Studies have not found sex to be a predisposing factor for atopic dermatitis or food allergy 39–41 . It is possible that there is some unknown variable that could explain the result.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this is unclear. Studies have not found sex to be a predisposing factor for atopic dermatitis or food allergy 39–41 . It is possible that there is some unknown variable that could explain the result.…”
Section: Discussionmentioning
confidence: 99%
“…Canine AD is a common, genetically predisposed, inflammatory and pruritic skin disease with varied clinical features most commonly associated with IgE antibodies to environmental allergens (Halliwell 2006, Miller and others 2013, Hensel and others, 2015). There are no pathognomonic clinical signs to definitively diagnose AD on presentation (Hensel 2015); therefore, a thorough and regimented diagnostic plan is imperative for diagnosing AD.…”
Section: Discussionmentioning
confidence: 99%
“…Epidermal barrier function is impaired in cAD, suggesting a route for epicutaneous sensitization (Santoro et al, 2015). The pathogenesis of cAD is multifactorial and complex interactions between genetics and environment are hypothesized, as in human AD (Bizikova et al, 2015). …”
Section: Introductionmentioning
confidence: 99%